Is China Growing Dirty? A Cointegration Analysis with Structural Breaks - Mustafa Naimoğlu; Sefa Özbek (İktisat Politikası Araştırmaları Dergisi)
Economic growth and development are some of the most important macroeconomic targets for national economies. Many ways exist for achieving these goals, and ensuring sustainability has a very important place. How much economic growth and development need to contribute to increasing human welfare, the quality and characteristics of growth in a national economy become important. This study examines the relationships among energy consumption, trade liberalization, economic growth, and CO2 emissions over the sample period of 1971-2018 in the Chinese economy, which saw a 393.64% per capita increase in energy use, 3,180.01% increase in gross domestic product per capita, and 610.515% increase in CO2 emissions per capita in 2018 compared to 1971. The study first tests the stationarity of the variables using the Zivot and Andrews (1992) unit root tests with structural breaks. The presence of long-term relationships among the variables was investigated using the Gregory and Hansen (1996) cointegration test, which includes structural breaks in the model. The short- and long-term coefficient estimations were analyzed using the Full Modified Ordinary Least Squares (FMOLS) and canonical cointegration regression (CCR) methods. Estimates for the short- and long-term coefficients were analyzed using the FMOLS and CCR methods. The results show that economic growth and energy consumption increase CO2 emissions in the short and long term. Therefore, pollution growth is determined to have taken place in China. This result stands out as an important problem in China. The high level of CO2 emissions in China and the fact that this problem has a significant weight on a global scale removes the problem from being local. Therefore, politicians need to take concrete steps immediately to solve this problem.